Pengaruh konsentrasi enzim chitosanase dan waktu inkubasi terhadap karakteristik chitooligosakarida dan aktivitas prebiotik dari cangkang kepiting bakau - Sri Winarti; Anugerah Dany Priyanto; Nanda Oktavia (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Mangrove crab shells are one of the wastes that are poorly utilized because it is usually only used for animal feed mixtures. Mangrove crab shells have a high enough chitin content so that it can be used as chitosan and then used as chitooligosaccharides that have the potential to have prebiotic activity. The study aimed to determine the effect of enzyme concentration and length of incubation time on the prebiotic characteristics and activity of chitooligosaccharides. Completely Randomized Design was used as a design experiment with a variable chitosanase enzyme concentration (0.5%, 1%, and 1.5%) and incubation time (1 hour, 3 hours, and 5 hours). The study shows that there is an interaction between the two variables in the viscosity parameter, degree of deacetylation, molecular weight, and degree of polymerization. The results showed that the best treatments were an enzyme concentration of 0.5% and a long incubation time of 5%, which resulted in chitooligosaccharides with characteristics: viscosity of 2.75 cPs, degree of deacetylation of 97.68%, the molecular weight of 546.99 Da, and degree of polymerization of 2.67. The best treatment tested the prebiotic activity of 1,18 for Lactobacillus acidophilus bacteria and 1,33 for Bifidobacterium breve bacteria. Hope this research would be an innovation in the production of a crabs shell or chitin’s source into prebiotic chitooligosaccharide and could boost the immune system.